Analysis Quality and Leadership on Organizational Citizenship Behavior and Performance in Government Service - Prastiwi; Mujanah, Siti (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to determine the effect of Quality and Leadership on Organizational Citizenship Behavior and Performance in Government Service. The method used is quantitative, with a sample in the study 50 respondents. statements on questioner based on survey kepuasan masyarakat (SKM) has adjusted research variables. Data analysis techniques using Smart PLS. The test results obtained Human Resource Quality haven’t significant on Employee Performance, Human Resource Quality haven’t significant on Organizational Citizenship Behavior, Leadership Style has significant on Organizational Citizenship, Leadership Style has significant on Organizational Citizenship Behavior, and Organizational Citizenship Behavior has significant on Employee Performance Government Service